2009
DOI: 10.1101/gad.1784309
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide replication profiles indicate an expansive role for Rpd3L in regulating replication initiation timing or efficiency, and reveal genomic loci of Rpd3 function in Saccharomyces cerevisiae

Abstract: In higher eukaryotes, heritable gene silencing is associated with histone deacetylation and late replication timing. In Saccharomyces cerevisiae, the histone deacetylase Rpd3 regulates gene expression and also modulates replication timing; however, these mechanisms have been suggested to be independent, and no global association has been found between replication timing and gene expression levels. Using 5-Bromo-29-deoxyuridine (BrdU) incorporation to generate genome-wide replication profiles, we identified >10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
129
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(132 citation statements)
references
References 60 publications
2
129
1
Order By: Relevance
“…Data generated by microarray-based assays support the view that initiation of DNA replication follows a temporal program that is imposed by epigenetic mechanisms and is stably transmitted to daughter cells (Knott et al 2009;Raghuraman et al 2001). However, this model has been recently challenged by Shao and colleagues, who showed that all yeast chromosomes VI have different replication profile when analyzed at the singlemolecule level (Czajkowsky et al 2008).…”
Section: Dna Replication Programs: the Yeast Paradigmmentioning
confidence: 75%
See 1 more Smart Citation
“…Data generated by microarray-based assays support the view that initiation of DNA replication follows a temporal program that is imposed by epigenetic mechanisms and is stably transmitted to daughter cells (Knott et al 2009;Raghuraman et al 2001). However, this model has been recently challenged by Shao and colleagues, who showed that all yeast chromosomes VI have different replication profile when analyzed at the singlemolecule level (Czajkowsky et al 2008).…”
Section: Dna Replication Programs: the Yeast Paradigmmentioning
confidence: 75%
“…Hence, early origins replicate late when they are moved to late-replicating regions of the genome, whereas initiation at late origins is advanced when they are moved to early regions (Lucas and Feng 2003). Multiple factors affect replication timing in eukaryotic cells, including histone modifications, subnuclear localization, and gene activity (Hiratani et al 2009;Knott et al 2009;Lucas and Feng 2003). Replication timing is also controlled by checkpoint kinases, which detect stalled replication forks and prevent the activation of late origins until the replication stress is relieved (Tourriere and Pasero 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The replication time of telomere proximal regions is regulated by telomere length with shorter telomeres replicated earlier (Bianchi and Shore 2007;Lian et al 2011). Chromatin modifications have also been implicated in the regulation of replication origin activation time (Vogelauer et al 2002;Knott et al 2009); however, no clear correlations between specific chromatin modifications and replication time have been identified. In summary, the molecular mechanisms responsible for differences in replication time remain elusive (Sclafani and Holzen 2007).…”
mentioning
confidence: 99%
“…Because of these reports, many studies have tried to establish the parameters of chromatin that influence origin firing. We and others have shown that histone modifications, especially acetylation, can affect origin timing and efficiency (Vogelauer et al 2002;Iizuka et al 2006;Knott et al 2009;Unnikrishnan et al 2010). Moreover, genome-wide nucleosome mapping showed that nucleosome positions dictate the association of Mcm2-7 with origins (Belsky et al 2015).…”
mentioning
confidence: 99%